1997
DOI: 10.1111/j.1432-1033.1997.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycothiol‐Dependent Formaldehyde Dehydrogenase, A Prokaryotic Medium‐Chain Dehydrogenase/Reductase, Phylogenetically Links Different Eukaroytic Alcohol Dehydrogenases Primary Structure, Conformational Modelling and Functional Correlations

Abstract: Prokaryotic mycothiol-dependent formaldehyde dehydrogenase has been structurally characterized by peptide analysis of the 360-residue protein chain and by molecular modelling and functional correlation with the conformational properties of zinc-containing alcohol dehydrogenases. The structure is found to be a divergent medium-chain dehydrogenase/reductase (MDR), at a phylogenetic position intermediate between the cluster of dimeric alcohol dehydrogenases of all classes (including the human foims), and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 39 publications
3
46
0
Order By: Relevance
“…Sequence analysis showed that the enzyme is a divergent medium-chain dehydrogenase/reductase (103). The cloned His 6 -tagged M. tuberculosis enzyme proved difficult to purify in active form when expressed in E. coli or M. smegmatis (149).…”
Section: Mscr Msno Reductase/formaldehyde Dehydrogenasementioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis showed that the enzyme is a divergent medium-chain dehydrogenase/reductase (103). The cloned His 6 -tagged M. tuberculosis enzyme proved difficult to purify in active form when expressed in E. coli or M. smegmatis (149).…”
Section: Mscr Msno Reductase/formaldehyde Dehydrogenasementioning
confidence: 99%
“…8. MSH reacts spontaneously with formaldehyde to produce an adduct, H 2 C(OH)SM, which is a substrate for the formaldehyde dehydrogenase AdhE2 (103). AdhE2-catalyzed oxidation of formaldehyde to formate detoxifies formaldehyde originating from metabolic or environmental sources.…”
Section: Overviewmentioning
confidence: 99%
“…8) S-Hydroxymethyl-mycothiol is formed nonenzymatically from mycothiol and formaldehyde in Gram-positive methylotrophs; mFADH then catalyzes NAD-dependent dehydrogenation of S-hydroxymethylmycothiol to produce S-formyl-mycothiol. 9) The genetic organization in the vicinity of the mFADH gene in the N9T-4 genome was compared with that in the R. erythropolis PR4 and R. jostii RHA1 genomes 10) which have been completely sequenced (Fig. 1a).…”
Section: Resultsmentioning
confidence: 99%
“…The first was for MSH-dependent formaldehyde dehydrogenase of Amycolatopsis methanolica (8,16), whose protein sequence is 80% identical to Rv2259 of M. tuberculosis (Sanger Centre). A disulfide reductase (Rv2855) initially designated as a glutathione reductase (4) was cloned and expressed in M. smegmatis and was shown to have specificity for mycothiol disulfide, alternatively designated mycothione (17,18).…”
Section: Discussionmentioning
confidence: 99%